Redefining the treatment of Chagas disease: a review of recent clinical and pharmacological data for a novel formulation of nifurtimox. - Jaime Altcheh; Ulrike Grossmann; Heino Stass; Martin Springsklee; Facundo Garcia-Bournissen (PLoS Neglected Tropical Diseases)
Nifurtimox has been used for over 50 years to treat patients with Chagas disease, a potentially life-threatening neglected tropical disease caused by the protozoan parasite Trypanosoma cruzi. Without effective antitrypanosomal treatment, the infection can persist and progress to a chronic, often debilitating, clinical form. Migration and urbanization, as well as the shifting distribution of the parasite's insect vector, have contributed to the emergence of Chagas disease as a global health threat. Administration of nifurtimox involves adjusting the dose for age and body weight. Particularly for children, this often requires the previously available 120 mg tablet to be divided manually, which could be problematic. To address this challenge, a new formulation tablet of nifurtimox was developed. Available in two dose strengths, 30 mg and 120 mg, the new formulation tablets contain a functional score line to facilitate accurate division. In addition, the formulation now allows rapid and easy dispersion in water to form a slurry for use by patients with difficulty swallowing tablets. These features enable more accurate body-weight-based and age-appropriate dosing and administration, which should prove beneficial for younger patients, including newborns and babies with a body weight ≥2.5 kg. Development of the new formulation nifurtimox tablets was guided by substantially updating pharmacological and clinical knowledge of the drug to meet current standards and regulatory requirements. This was achieved by conducting a substantial array of additional non-clinical and clinical studies to better understand and characterize clinically relevant aspects of nifurtimox pharmacokinetics. The efficacy and safety of the new tablet in children with Chagas disease was subsequently demonstrated in a large prospective randomized clinical trial with prolonged follow-up. In the present paper, we review key findings that contributed to the successful clinical development of the new formulation nifurtimox tablet, the availability of which redefines the treatment of young patients with Chagas disease.